(untitled) (International Journal of Engineering and Computer Science, 2014)
The population of India is growing expeditiously with a national average growth rate of 1.41per cent per annum (Census of India, 2011). Increase in population and economic activities the travel demand has increased many folds. The inadequate public transport and the easy availability of financing facilities for private vehicles have resulted in increased vehicle ownership levels and their usage. Crumbling road infrastructure coupled with the increase in vehicle population has hurled the city’s traffic problem to ungovernable levels. There could be two possible viewpoints to solve this problem. First viewpoint is to come up with an infrastructure which involved wider roads, expressways, flyovers and bypasses. But in developing age of developing countries like India, Malaysia, Sri Lanka, etc money and space are very big concerning problem. Second viewpoint is to manage the existing traffic load on the same available infrastructure, with the use of technology. This calls for the vital need of Intelligent Transportation Systems (ITS), which helps in managing billion vehicles that are running on the roads. This paper mainly focused on image enhancement and segmentation phase of high security registration number plate recognition system. We present the Hybrid approach of the Boat operator filter and Montane filter, which is very useful and successful filtering technique for image enhancement and edge detection.